1993
DOI: 10.1159/000292635
|View full text |Cite
|
Sign up to set email alerts
|

Sub-50 Oral Contraceptives Affect Folate Kinetics

Abstract: The effects of long-term use of oral contraceptives containing less than 50 µg of estrogen (sub-50 OCs) on the kinetics of folic acid monoglutamate, vitamin B12 levels, and iron status have been studied in 29 OC users (Marvelon®) and in 13 women without OC use serving as controls. At 210 min after oral folate loading the median serum folate concentration was significantly lower in OC users when compared to the control group. OC users showed significantly higher total iron binding capacity and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The post hoc analyses suggested that all three might be important here. First, vitamin B 6 levels decreased during treatment, an effect that has also been shown in oral contraceptive users (36). This might seem contradictory because vitamin B 6 is a cofactor in the transsulfuration pathway, which thereby could be impaired as well.…”
Section: Discussionmentioning
confidence: 98%
“…The post hoc analyses suggested that all three might be important here. First, vitamin B 6 levels decreased during treatment, an effect that has also been shown in oral contraceptive users (36). This might seem contradictory because vitamin B 6 is a cofactor in the transsulfuration pathway, which thereby could be impaired as well.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in most studies there were no controls for dietary folate intake, vitamin supplement use, smoking, or alcohol use. [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] In addition, other factors not considered by many investigators include differences in the specific type of hormone used in the OCs, 58,59 compliance with the OC regimen, 44,58,59 and duration of OC use. 50,58 Folate status in these earlier studies was, in most cases, based solely on a comparison of serum folate concentration between groups of OC users and non-users.…”
Section: Folatementioning
confidence: 99%
“…32 More recently conducted studies, designed to evaluate the effect of OC use on folate status, have included measures of RBC folate concentration; however, as with studies measuring only serum folate concentration, the results have been equivocal. [46][47][48]50,51,[60][61][62] In the studies from which it was concluded that OC use negatively affected folate status, none controlled for all potentially confounding variables, including differences in dietary intake and use of folic acid-containing supplements. 46,48,60,62 Of those studies that controlled for dietary intake, with one exception, 62 no difference in RBC folate concentration between OC and non-OC users was detected.…”
Section: Folatementioning
confidence: 99%
See 1 more Smart Citation
“…The information that is available in the literature concerning the serum levels of folate (folic acid) in women using oral contraceptive pills is still somewhat conflicting. Some studies have shown diminished serum or plasma concentrations of fo-late in users of oral contraceptives when compared to controls [23,24], whereas others have found similar levels of folate in oral contraceptive users and non-pregnant female volunteers [25][26][27][28][29]. These divergent observations are hard to reconcile.…”
mentioning
confidence: 99%